Traditional medicine Bazi Bushen potentiates immunosurveillance of senescent liver cancer cells via cGAS-STING signaling activation in macrophages - Xing, Fuxue; Lv, Hongwei; Xiang, Wei; Wang, Liang; Zong, Qianni; Lv, Guishuai; Liu, Chunying; Feng, Qiyu; Wang, Hongyang; Yang, Wen (Cancer letters, 2025)
Senescent cancer cells often evade immune clearance to exert profound effects on cancer progression and therapy resistance. Improving immunosurveillance to eliminate senescent cancer cells is a crucial measure to enhance anti-cancer therapy. Bazi Bushen (BZBS) is a traditional medicine with the function of relieving fatigue and delaying ageing, but its role in tumor treatment remains poorly understood. Herein, we find that BZBS promotes immunosurveillance of both chemotherapy- and oncogene-induced senescent liver cancer cells, further leading to enhanced chemotherapy efficacy and dramatic tumor repression in mice. Mechanistically, BZBS induces mitochondrial DNA leakage by mitochondrial damage to further activate cGAS-STING signaling in macrophages. Subsequently, cGAS-STING signaling activation in macrophages recruits CD8+ T cells into tumor and promotes the anti-tumor activity of CD8+ T cells to eradicate senescent cancer cells. Furthermore, host STING is responsible for BZBS-mediated immunosurveillance of senescent liver cancer cells in mice. Therefore, our findings unveil the role of traditional medicine BZBS in activating cGAS-STING signaling and potentiating senescence immunosurveillance to enhance anti-cancer therapy. •BZBS enhances chemotherapy efficacy and represses tumor progression in mice.•BZBS promotes immunosurveillance of senescent liver cancer cells.•BZBS induces mitochondrial DNA leakage to activate cGAS-STING signaling in macrophages.•Host STING is responsible for BZBS-mediated immunosurveillance of senescent liver cancer cells.